Education for Global Citizenship: Promoting Democracy - Manuela Mesa (Universidad Autónoma de Madrid, 2019)
This paper makes a reflection on the role of education in the current international context, marked by profound changes and by a situation of uncertainty and instability and reverse in rights. It discusses the various interpretative frameworks that explain the current world and that are articulated around the global-local axis and ethnic-national identities and multiple identities. In a world characterized by the complexity and speed of changes, it is very important to overcome the the compartmentalization of knowledge in areas such as mathematics, social, language, etc and look for global approaches. From the cognitive point of view, there is a need to modify the way of organizing the knowledge and put it in relation to new concepts. It's about creating emancipatory narratives that they put in the centre of the human person and the relationship between peace, development, human rights and justice. From a methodological point of view, it proposes strategies to apprehend reality, from the use of tools that combine rational aspects, visual, emotional and numeric and that stimulate creativity and the "moral imagination". And from the strategies of action, educational practice must overcome the school framework and taking into account other areas to non-formal education and in close collaboration with social organizations, to deal with the large global-local problems related to violence, inequality, environmental sustainability and global warming. Education as a transformative practice cannot be outside of the major challenges facing humanity at the national and multilateral. The 2030 Agenda and the Sustainable Development Goals gives opportunities for the consolidation of the Education for Global Citizenship.